Depression, Anxiety, and Stress among Secondary School Teachers in Klang, Malaysia - Othman, Zahiruddin; Sivasubramaniam, Vevehkanandar (Japan International Cultural Exchange Foundation, 2019)
Background: Teaching has been identified as a highly stressful job. Recent changes such as the increasing use of information technology and diversity of teacher's role potentially increase the stress even further. Objectives: This study aimed to determine the prevalence of psychological distress of depression, anxiety, and stress among secondary school teachers in Klang zone, Malaysia. Methods: A total of 356 teachers from 6 randomly selected secondary schools in Klang zone were recruited into the study. The Malay Depression Anxiety Stress Scales (DASS) was employed to measure the psychological distress depression, anxiety, and stress. Results: The teachers had a high prevalence of depressive (43.0%), anxiety (68.0%) and stress (32.3%) symptoms. While severe to extremely severe depression, anxiety and stress were reported by 9.9%, 23.3% and 7.0% of subjects, respectively. Depression, anxiety, and stress were consistently more common among teachers with socio-demographic and work-related characteristics such as female, lowest educational status, having 1-3 children, staying with in-laws, shorter distance to school, living in a high-rise building and own house. Conclusions: The prevalence of depression, anxiety, and stress were high among secondary schools teachers. Appropriate steps should be taken to improve the mental health of teachers, thereby ensuring good quality education.